Association of Lower Urinary Tract Symptoms with Metabolic Disorders, Neurological Dysfunction, and Reactive Arthritis: A Community-Based Cross-Sectional Study - Tahir Siddique, Marryam Khalid, Zia ul Haq, Nasar Iqbal Ranjha, Muhammad Aitmaud Uddolah Khan, Rafaqat Malik (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Lower urinary tract symptoms (LUTS) are highly prevalent and increasingly recognized as manifestations of systemic disorders rather than isolated urological conditions. Emerging evidence suggests strong associations between LUTS and metabolic abnormalities, neurological dysfunction, and inflammatory diseases such as reactive arthritis, particularly in urban populations with rising cardiometabolic burden. Objective: To evaluate the association of lower urinary tract symptoms with metabolic disorders, neurological dysfunction, and reactive arthritis in a community-based population. Methods: This cross-sectional study was conducted from August 2022 to August 2023 at Lahore General Hospital, Lahore, and Pakistan Institute of Medical Sciences (PIMS), Islamabad. A total of 120 participants aged 30–70 years were enrolled. LUTS severity was assessed using the International Prostate Symptom Score (IPSS). Metabolic parameters, neurological status, and presence of reactive arthritis were evaluated. Statistical analysis included chi-square testing and multivariate logistic regression, with significance set at p < 0.05. Results: The prevalence of LUTS was 68.3%, with moderate-to-severe symptoms observed in 45.8% of participants. Metabolic syndrome was significantly associated with LUTS (OR = 3.42, 95% CI: 1.85–6.31, p < 0.001), followed by neurological dysfunction (OR = 2.76, 95% CI: 1.41–5.40, p = 0.003) and reactive arthritis (OR = 2.19, 95% CI: 1.05–4.56, p = 0.035). Individual metabolic components including obesity, diabetes, and hypertension also showed significant associations. Conclusion: LUTS are strongly linked with metabolic, neurological, and inflammatory conditions. Integrated multidisciplinary management targeting underlying systemic disorders may improve clinical outcomes and quality of life. Keywords: Lower urinary tract symptoms; metabolic syndrome; neurological dysfunction; reactive arthritis; inflammation; IPSS; community-based study.